Tanggungjawab Notaris dalam Pembuatan Akta Para Pihak Di bawah Tekanan dan Paksaan - Dimas Almansyah; Mohamad Fajri Mekka Putra (Jurnal USM Law Review)
Notaries have a very important role in meeting the community's needs to build order, legal protection, and law related to the certainty of their authority in doing authentic deeds. Parties who come to the notary as drivers may be under pressure or coercion. The purpose of this study is to find out how the role and responsibilities of a notary in making a deed when the appearer is under pressure and coercion. The research method in this research is normative juridical. The results of this study indicate that the role of a notary is to refuse to make a deed for reasons,  which is contrary to the law and plays a role in providing legal counseling regarding the legal implications if the agreement is made under pressure and coercion according to its authority in the UUJN. In addition, it is the responsibility of the notary if he knows the condition of one of the appearers under pressure and coercion but still makes him responsible for committing an unlawful act by siding with one of the appearers, being dishonest, and untrustworthy.  However, if the notary does not know it, the notary cannot be said to be negligent and responsible because the notary has no obligation to investigate material truths and the notary only pours into the deed the things that appear before him